PENGARUH STABILITAS PENJUALAN (SP) DAN STRUKTUR AKTIVA (STA) TERHADAP STRUKTUR MODAL (STM) PADA INDUSTRI FOOD AND BEVERAGES - Dori HP Putra (LP2M Universitas Bina Bangsa, 2024)
This study aims to determine the Stability of Sales and Asset Structure Relative to Capital Structure in Food and beverages companies listed on the Indonesia Stock Exchange for the 2021-2023 period. This study uses secondary data. The sample used is 5 Food and beverages companies on the Indonesia Stock Exchange during the 2021-2023 research period. the independent variable in this study is Sales Stability, and Asset Structure. Sampling in this study uses a purposive sampling technique. The data analysis methods used are classical assumption test, hypothesis test, F test and T test. Based on the results of this study, it is known that there is no significant influence between Sales Stability on Capital Structure in food and beverages companies and there is a significant influence between Asset Structure and Capital Structure in food and beverages companies The most dominant factor that affects the capital structure is the Asset Structure with a large influence of 27.4%